On the Characterisations of Curves with Modified Orthogonal Frame in ???? - Özel, Şeyda; Bektaş, Mehmet (My University, 2022)
This study analyses (??, ??)-type slant helices in compliance with the modified orthogonal frame in 3-dimensional Euclidean space (??3). Furthermore, we perform some characterisations of curves with modified orthogonal frames in ??3.
Keywords: Modified orthogonal frame; helices; (k; m)-form Slant Helices